The relationships between plasma cholesteryl polyunsaturated fatty acids, age and atherosclerosis. Issue 527 (September 1969) - Kingsbury, K. J.; Stovold, R.; Morgan, D. M.; Brett, C. G.
Abstract : The ages, plasma cholesteryl dienoic acid, 2-hr blood sugar and plasma cholesterol concentrations of 146 patients with aorto-iliac and femoro-popliteal atherosclerosis, were compared with their arterial lesions classified into occlusions, irregularities and stenoses by pulses and arteriograms. The arterial lesions were also compared with the patient's prognosis in terms of the development of angina or myocardial infarction. The results showed that reduced concentrations of cholesteryl dienoic acids were specifically related to an increase in the number of arterial occlusions, independently of the patients' ages, plasma cholesterol and 2-hr blood sugar levels, arterial irregularities or stenoses. The arterial occlusions in turn related to the development of myocardial infarction but not angina. It is concluded that a relationship existed between the reduced concentrations of cholesteryl dienoic acids and the occlusive element of human atherosclerosis which is a major factor in the patient's prognosis.